Inflammatory Myofibroblastic Tumor of the Kidney: A Rare Renal Tumor - Alvin Jose Pothadiyil; Suresh Bhat; Fredrick Paul; Jithesh Mampatta; Mahesh Srinivas (Journal of Clinical and Diagnostic Research, 2016)
Inflammatory Myofibroblastic Tumour (IMT) or ‘pseudotumour’ of the kidney is a rare benign tumour of unknown aetiology affecting mostly young adults. A subset of IMT is neoplastic and harbours translocations of activin receptor-like kinase-1 (ALK-1) gene and can recur or rarely metastasize. Presentation varies from an incidentaloma to gross haematuria. Clinical examination and radiological investigations are usually inconclusive. Often, biopsy is inconclusive necessitating a management similar to that of Renal Cell Cancer (RCC). Diagnosis is based on immunohistochemistry. We are reporting a case of IMT in a 50-year-old male patient who presented with left flank mass which on evaluation was suggestive of left renal cell carcinoma. Excision of the tumour, histopathological examination and Immunohistochemistry proved the tumour to be IMT.